THE EFFECT OF VITAMIN D SUPPLEMENTATION ON GESTATIONAL DIABETES (The Research of Medical Science Review, 2024)
Introduction: In view of the growing prevalence of gestational diabetes mellitus (GDM), a great deal of study has been done to determine the link between vitamin insufficiency and GDM. All the same, Pakistan has not generated many clinical research studies. Objective: The goal of this study is to determine how vitamin D supplementation impacts the GDM and vitamin D insufficiency in pregnant women. Method: During patients' prenatal checks at the hospital, information was gathered from them using a self-made questionnaire. Serum vitamin D testing was done on patients aged 18 to 40 who were diagnosed with gestational diabetes between the 24th and 28th week of pregnancy. Group A and B were formed from 106 GDM patients who were vitamin D insufficient. Group B, the control group, received no therapy for six weeks while Group A received an interventional dosage of vitamin D (50,000 IU) twice at two-week intervals. Group A received only two doses totaling fifty thousand units of dosage. The two groups' serum FBS, HbA1c, and vitamin D levels were compared. Findings: Following the intervention, there was a significant drop in HbA1c (5.764), a rise in Vit D (23.70 ng/mL), and a change in FBS (97.55 mg/dL),Results: According to descriptive data. Significant differences were verified by a Mann-Whitney U test, which rejected the null hypothesis for all variables (p < 0.05).Conclusion: The group that received the intervention showed better results than the control group, including better glycemic control and higher levels of vitamin D. These results highlight the intervention's potential effectiveness in managing gestational diabetes and highlight how important it is to optimal mother health.